The Use of Influence Strategies in Interfirm Relationships in Industrial Product Channels - Frazier, Gary L.; Rody, Raymond C. (Journal of Marketing, 1991)
The authors seek to extend theory and empirical findings on interfirm influence strategies by examining their use in channel relationships between suppliers and distributors of industrial products. Research hypotheses are developed, centering on the reciprocal use of noncoercive and coercive influence strategies by the supplier and the distributor in the channel dyad and on the interrelationships of these strategies with the interfirm power, latent conflict, manifest conflict, and conflict resolution constructs. Data from a national survey of industrial distributors are used in testing the research hypotheses, which are generally supported by the empirical results.